Permeabilisation of the Outer Membrane of Escherichia coli for Enhanced Transport of Complex Molecules - Casas-Rodrigo, Ivan; Vornholt, Tobias; Castiglione, Kathrin; Roberts, Tania Michelle; Jeschek, Markus; Ward, Thomas R.; Panke, Sven (Microbial Biotechnology, 2025)
The bacterial envelope plays a critical role in maintaining essential cellular functions by selectively regulating import and export. The selectivity of this envelope can restrict the utilisation of externally provided compounds, thereby restricting the functional space of cellular engineering. This study systematically investigates the potential of large pore outer membrane proteins (OMPs) to enhance outer membrane permeability for diverse challenging compounds. We focus on the general porin OmpF, which facilitates the diffusion of water and small molecules, and specific OMP transporters FhuA and FepA, which mediate the translocation of small hydrophilic compounds. Through comprehensive characterisation, we evaluate the effects of recombinant expression of OMPs and engineered variants for small and hydrophilic compounds, aromatic molecules and bulky molecules and apply our findings to address two critical contemporary transport challenges: the uptake of large metal-containing cofactors for artificial metalloenzymes and non-permeant fluorescent Halo-ligands for in vivo protein labelling. Notably, we demonstrate significant improvements in ArM-catalysis and labelling. This study provides a practical guide for designing experiments that include outer-membrane-transport-limiting steps. This study highlights the potential of engineered OMPs to overcome the limitations imposed by the cell envelope, enabling the incorporation of complex molecules and expanding the frontiers of cellular engineering.
CRIS-Team Scopus Importer:2025-04-01
Keywords: cell envelope; OMP; outer membrane; permeability; pore